ASSESSMENT OF C-REACTIVE PROTEIN AND OXIDATIVE/ANTIOXIDATIVE STATUS IN CHILDREN WITH ACUTE BACTERIAL MENINGITIS - IMAD A.J. THANOON; MUS'AB M. KHLAF; MAHMOOD K. OGLAH (Universiti Sains Malaysia, 2009)
The objectives of this study were to compare the serum levels of C-reactive protein (CRP), serum malondialdehyde (MDA), antioxidant parameters [represented by serum ferritin, uric acid and totalantioxidant status (TAS)] in children with bacterial meningitis with a control group. Twenty-seven children with bacterial meningitis were included in this study. Thirty apparently healthy childrenwere also included as the control group. Assays of serum CRP, uric acid, ferritin and TAS were performed on samples from controls and from patients prior to antibiotic therapy. After two weeksof antibiotic therapy, assays of the same parameters were repeated in the patients. A significant rise in the serum levels of MDA and CRP, and a significant reduction in serum uric acid levels andTAS were noted in children with acute bacterial meningitis (before therapy) compared to controls. Serum ferritin levels showed no significant differences. When measured parameters of children withbacterial meningitis after therapy were compared with those of the controls, highly significant differences in the mean serum levels of uric acid, CRP and TAS were noted. There were no significant differences in the mean serum ferritin levels. Serum oxidative/antioxidative balance shifted to the oxidative side in meningitis patients before therapy, and improved after therapy.Elevation of CRP in cases with bacterial meningitis may reflect its importance as an aid in the diagnosis of such cases.